PENERAPAN NILAI – NILAI FILSAFAT DALAM PENDIDIKAN DI ERA GLOBALISASI (SEKOLAH METHODIST–5 MEDAN) - Hasibuan, Rey Artha Dika Br; Imran, H. Zulfi (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2025)
This research aims to explore the application of philosophical values in education in the era of globalization. Philosophy was originally known as the mother of all sciences, because it is considered capable of providing answers to various questions about everything, both related to the universe and to human life and all its problems. The method used in this research is descriptive qualitative method. To improve the quality of educational philosophy in the era of globalization, various innovations are needed, both in curriculum development, learning methods, and the provision of educational facilities and infrastructure, so that students feel interested and encouraged to learn and discover the basic concepts of a science based on their own hypotheses. This kind of learning process will be more memorable and meaningful, so that understanding of the basic concepts of science will not be quickly forgotten. For learning to be meaningful, it is important to understand the concepts so that they can connect one concept with another. The application of philosophical values in education at Sekolah Methodist-5 Medan has a positive impact on student development. Philosophy of education aims to build a foundation of critical learning and broad thinking.